Urban ecology transformation: achieving carbon neutrality within Elmina Business Park - Mat Ghazi, Muhammad Afif Abidi; Abu Bakar, Aniza; Othman, Rashidi (Department of Landscape Architecture, KAED, IIUM, 2024)
Eco-urban has become a widespread concept across the globe in urban development focusing on urban development and the natural environment at the same time. Several frameworks have been created in response to this approach such as low-carbon city framework (LCCF), green city concept, and green technology innovations. Urban areas typically face several climate challenges and problems such as greenhouse gas (GHG) emissions, environmental pollution, and urban heat island (UHI) which require ecological urban approaches as the core of the solution. In 2022, Malaysia (330803km2) produced 291.07 MtCO2e equivalent to 0.87kg/m². This research provides a framework to measure and optimise both carbon emission and carbon sequestration within commercial-industrial areas. The research highlights the practical application of ecological approaches and technologies to reduce carbon emissions while enhancing carbon sequestration, offering actionable insights for achieving carbon neutrality in similar urban developments. The study took place at Elmina Business Park (EBP), a 0.63km2 commercial-industrial centric area, potentially emitting an excessive amount of carbon with the current conventional approach to urban development. This study analysed the existing landscape masterplan of EBP to identify the potential of carbon emission and carbon sequestration rate in the area. This study aims to enhance the existing landscape masterplan of EBP by reducing carbon emissions and increasing the carbon sequestration rate. The study uses a mixed-method strategy, encompassing document analysis of existing low-carbon city frameworks and engaging in semi-structured interviews involving two landscape architects from developer, and landscape consultants of EBP. This is to understand the approach of the consultant for a low-carbon landscape masterplan for EBP while studying their proposed landscape masterplan in terms of carbon emission and carbon sequestration calculation. Based on initial findings, the area of the selected site potentially produces approximately 13012.94 tCO2e/year. After anticipation of tree growth reaching their mature size in fifteen years, the existing landscape masterplan only can sequester 1765.2 tCO2e which means 117.71 tCO2e/year. The proposed landscape masterplan with a set of landscape design strategies is expected to significantly decrease the carbon emission to 4748.32 tCO2e/year and increase the carbon sequestration rate to 1400 tCO2e/year, 2.22kg/m². This 88 study outlined the key strategies to mitigate carbon and improve carbon sequestration rate in urban context which can be the guideline for future sustainable urban planning.